Developing agricultural value chains - Kolavalli, Shashidhara (International Food Policy Research Institute, 2019)
This chapter examines and compares four important but different types of value chains in Ghana: two export crops—cocoa and pineapples, and two import-substitution crops—rice and tomatoes. Apart from cocoa, these crops have under-exploited opportunities, and we examine the opportunities and constraints along their value chains, and the roles that the public sector has or might need to play. This leads to some more general conclusions about the best ways to develop these and related agricultural value chains in Ghana.